Crystal‐less oscillator calibration using serial data as frequency reference. Issue 16 (1st August 2018) - Yang, Wendi; Jiang, Hanjun; Wang, Zhihua
Abstract : A frequency calibration method for a crystal‐less current‐controlled ring oscillator is presented. It uses a serial data signal from another chip as the frequency reference. The proposed calibration circuit is composed of the coarse calibration and the fine calibration circuit. The coarse calibration circuit controls a binary weighted biasing current source array, while the fine calibration circuit generates a pulse‐width‐modulation (PWM) signal to control a switched biasing current source. The duty cycle ratio of the PWM signal is obtained by measuring the frequency ratio error between the oscillator output and the reference signal. An auto‐correlation‐based method is proposed to calculate the frequency ratio error. The 8 MHz ring oscillator in together with the calibration circuit has been fabricated in a 0.13 μm CMOS process. Measured results on 24 chips show that the relative frequency error is reduced to 0.0239% (mean offset + 3 σ ) after calibration. The reported oscillator shows advantages in accuracy, power consumption and chip area.